PENGARUH STRATEGI LAYOUT DAN LOKASI TERHADAP MINAT BELI KONSUMEN PADA FRANCHISE O’CHICKEN DI PEKANBARU - Putra Ona Hadi M.Hafiz; Daulay Nauli Iwan; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of (1) layout and location on buying interest, (2) layout on buying interest, and (3) location on buying interest. The sample in this study was taken using probability sampling technique, namely sampling by providing equal opportunities for each element of the population to be selected as sample members. The questionnaire was addressed to consumers of the O'Chicken franchise in Pekanbaru. The number of sample population used is 75 respondents from O'chicken franchise consumers in Pekanbaru. The data obtained were analyzed using multiple linear regression to determine the effect of the relationship between the independent variable and the dependent variable through the IBM SPSS Statistic 25.0 software. The results showed that (1) layout and location simultaneously had a positive and significant effect on the consumer buying interest variable of 48.60%, (2) layout had no significant effect on consumer buying interest, and (3) location had a positive and significant effect on consumer buying interest.Keywords: Layout, Location, and Buying Interest